Vanishing White Matter Disease: A Case Report and Review of Literature - Ali, Sana; Nadeem, Muhammad Sohaib; Shabab, Amir; Ali, Ujala (Pakistan Armed Forces Medical Journal, 2025)
Vanishing white matter disease is an autosomal recessive hereditary condition of brain. It may have variable phenotypic presentations but is more frequently encountered in younger age group. It is characterized by progressive encephalopathy and episodic neurological decline with predominant feature of cerebellar ataxia. Initial symptoms are preceded by a history of minor trauma, infection or stress. We present here a classic case of vanishing white matter disease diagnosed on Magnetic Resonance Imaging, documented in a four-year-old girl who presented with gait disturbance and progressive neurological deficits following a fall from bike.